The phenomenon of online stock trading in Korea : facts and implications. - Soegiarto Fany. (2008)
In our dissertation, we analyze the fundamental factors driving the rapid growth of online stock trading in Korea. We then examine the implications of online trading on the competitive environment of Korea’s retail brokerage industry and the liquidity, volatility, cost structure and efficiency of the stock market.